Particle tracking analysis of a rotor in ground effect - Rovere, F.; Barakos, G.N.; Steijl, R. (My University, 2020)
In the present work, computational fluid dynamics (CFD) is used to predict the behavior of ground particles, uplifted by a two-bladed rotor. The paper focuses on defining a safety area where the presence of particles can be considered as negligible, and compare this area with other distance based criteria. Using data of three different aircraft, scaling factors have been used to take into account the different size of the small-rotor studied and real case scenarios. The results show how heavier helicopters may generate the most dangerous situations, in terms of presence of particles in a delimited area.